Cover, Content, and Editorial Note from Borneo J Pharm Vol. 7 No. 4 November 2024 - Borneo J Pharm, Chief Editor of (Borneo Journal of Pharmacy, 2024)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published in November 2024. This edition contains ten articles: Pharmacology-Toxicology, Pharmacognosy-Phytochemistry, Pharmaceutical, Analytical Pharmacy-Medicinal Chemistry, Microbiology Pharmacy, Natural Product Development, and Clinical-Community Pharmacy. This edition includes writings from five countries: India, Indonesia, Saudi Arabia, Sudan, and Taiwan. The authors come from several institutions, including Institut Sains dan Teknologi Nasional, Taipei Medical University, Metro College of Health Sciences and Research, Galgotias University, Yogendra Nath Saxena College of Pharmacy and Research Centre, Shri Gopichand College of Pharmacy, Jadavpur University, Maulana Abul Kalam Azad University of Technology, Universitas Muslim Indonesia, Universitas Jenderal Soedirman, Akademi Farmasi Surabaya, University of Khartoum, National Medicines Quality Control Laboratory, Al Jouf University, Universitas Sari Mulia, Universitas Muhammadiyah Purwokerto, Universitas Muhammadiyah Kalimantan Timur, Universitas Muhammadiyah Palangkaraya, Universitas Wahid Hasyim, Universitas Jenderal Achmad Yani, and Ibrahim Adjie Primary Care. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors, could re-participate for publication in the next edition in March 2025. Wassalamu’alaikum Wr. Wb.